Effect of major cations (Ca2+, Mg2+, Na+, K+) and anions (SO 42−, Cl−, NO 3−) on Ni accumulation and toxicity in aquatic plant (Lemna minor L.): Implications For Ni risk assessment. (19th February 2013) - Gopalapillai, Yamini; Hale, Beverley; Vigneault, Bernard
Abstract: The effect of major cation activity (Ca 2+, Mg 2+, Na +, K + ) on Ni toxicity, with dose expressed as exposure (total dissolved Ni concentration NiTot ) or free Ni ion activity (in solution Ni 2+ ), or as tissue residue (Ni concentration in plant tissue NiTiss ) to the aquatic plant Lemna minor L. was examined. In addition, Ni accumulation kinetics was explored to provide mechanistic insight into current approaches of toxicity modeling, such as the tissue residue approach and the biotic ligand model (BLM), and the implications for plant Ni risk assessment. Major cations did not inhibit Ni accumulation via competitive inhibition as expected by the BLM framework. For example, Ca 2+ and Mg 2+ (sulfate as counter‐anion) had an anticompetitive effect on Ni accumulation, suggesting that Ca or Mg forms a ternary complex with Ni–biotic ligand. The counter‐anion of the added Ca (sulfate, chloride, or nitrate) affected plant response (percentage of root growth inhibition) to Ni. Generally, sulfate and chloride influenced plant response while nitrate did not, even when compared within the same range of Ca 2+, which suggests that the anion dominated the observed plant response. Overall, although an effect of major cations on Ni toxicity to L . minor L. was observed at a physiological level, Ni 2+ or NiTot alone modeled plant response, generally within a span of twofold, over a wide range of water chemistry. Thus, consideration of major cation competition for improving Ni toxicity predictions in risk assessment for aquatic plants may not be necessary. Environ. Toxicol. Chem. 2013;32:810–821. © 2013 SETAC